2011
DOI: 10.5897/ajmr10.721
|View full text |Cite
|
Sign up to set email alerts
|

A study on the vegetation recovery and crop pattern adjustment on the Loess Plateau of China

Abstract: Low vegetation coverage and irrational land use are regarded as two main factors in influencing soil loss. In order to improve vegetation recovery and to adjust land use pattern on the Loess Plateau, the data of precipitation, net primary productivity of vegetation, and eco-water requirement of main crops of key counties on the Loess Plateau are used in this paper. The concepts of utilization/adaptation capability of eco-water requirement are used and plotted against mean annual precipitation in the 1960s to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a report by the National Aeronautics and Space Administration (NASA), it was noted that China accounted for 25% of the global net increase in leaf area from 2000 to 2017, mainly as a result of afforestation and agricultural activities 6 . These studies have revealed the characteristics and causes of changes in greening at a global and national level; however, greening and its drivers vary significantly at a regional level due to environmental differences and socioeconomic development 7 9 . To implement ecological conservation and rehabilitation measurements, it is necessary to understand the spatiotemporal patterns and drivers of greening at a regional scale 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In a report by the National Aeronautics and Space Administration (NASA), it was noted that China accounted for 25% of the global net increase in leaf area from 2000 to 2017, mainly as a result of afforestation and agricultural activities 6 . These studies have revealed the characteristics and causes of changes in greening at a global and national level; however, greening and its drivers vary significantly at a regional level due to environmental differences and socioeconomic development 7 9 . To implement ecological conservation and rehabilitation measurements, it is necessary to understand the spatiotemporal patterns and drivers of greening at a regional scale 10 .…”
Section: Introductionmentioning
confidence: 99%